ANALISIS GAYA BAHASA PADA PUISI “ARITMIA” KARYA WIRA NAGARA - Juliyanto Sugihartono; Kosasih Ismail; Dida Firmansyah (IKIP Siliwangi, 2019)
In writing poetry each author has a style of language or technique that is his trademark. Some are accustomed to regular rhyme patterns, some are using rhetorical language styles. On this occasion the researcher wanted to find out what language style was used by Wira Nagara, in his poem entitled